Komunikasi, Legitimasi, dan Mediasi: Kritik atas Hegemoni Pemaknaan dalam Ruang Publik - Sindung Tjahyadi (Jurnal Filsafat "WISDOM", 2006)
The shoping of modern society  tends to refuse my theological legitimation. This pattern leads the society face serious problems because every domain in human life hasdeveloped in autonomous basic legitimation. There is no systemwhich organizes rules to knowledge, science, ethics, politics, andlaws. Mass media as free market of ideologiea is a power whichdominates the significance of  public sphere. This paper concernsin discussive the problem of communication as mediation ofmeaning in modern society. Based on an analysis ofcommunication aspects in modern society, we draw the prospectiveconclusion on which to build the future.